Comparison Study of Performance Analysis of Information System Using The Methods of End-User Computing Satisfaction and It Balance Score Card - Roy Sari Milda Siregar Siregar (Politeknik Negeri Semarang, 2019)
Evaluation of information system performance is needed to get an overview of the ease of end-users in utilizing a new technology. This study aims to evaluate the performance of information systems in a state-owned company (PT PLN Madya Langsa) based on an end-user perspective that is separated into two categories: employees and managers. The level of employee satisfaction (primary user) is measured using EUCS (aspect of: content, accuracy, format, ease of use, timeliness, and satisfaction). The manager's satisfaction level (secondary user) is measured by using IT BSC (aspect of: company contribution, user, operational excellence, and future orientation). The evaluation on the primary user showed that it was low at 25.6%, moderate at 56.64% and high at 18%. The percentage of user satisfaction with the information systems is 72.9% of the results expected by users. Meanwhile, evaluation on the secondary user obtained the following results: low at 10.5%, moderate 84.2% and high at 5.3%. The percentage of user satisfaction with the information system was 92.8% of the results that is expected by users. This study also discusses why there are differences in the percentage of primary user satisfaction compare to the secondary user and provides suggestions how to improve the level of satisfaction of the end users in the future.